PENGARUH INFLASI, JUMLAH UANG BEREDAR, dan SUKU BUNGA BANK INDONESIA TERHADAP NILAI TUKAR RUPIAH TAHUN 2013-2021 - Vania Fitri Latifah; Mohammad Sofyan; Ghita Yasaningthias (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the simultaneous effect of inflation, money supply, and Bank Indonesian interest rates on the Rupiah exchange rate in the 2013-2021 period. This research is a descriptive verificative study with a quantitative approach. The population in this study is all data on the monthly series of inflation, money supply, and Bank Indonesian interest rates against the Rupiah exchange rate for the period 2013-2021. The type of data used is secondary data series per month in 2013-2021 which is available and published by Bank Indonesia, Trade Data Unit and the Central Statistics Agency. Data analysis in this study was carried out using the technique of multiple linear regression analysis. The results of this research show that inflation, money supply, and Bank Indonesian interest rates have a significant influence on the Rupiah exchange rate in 2013-2021. The F test found a Sig F value of 0.00 < 0.05 with Fcount > from the Ftable, i.e. 189.5630 > 2.68.